Post-stroke depression: exploring gut microbiota-mediated barrier dysfunction through immune regulation - Jiang, Jia; Xie, Haihua; Cao, Sihui; Xu, Xuan; Zhou, Jingying; Liu, Qianyan; Ding, Changsong; Liu, Mi (Frontiers in Immunology, 2025)
Post-stroke depression (PSD) is one of the most common and devastating neuropsychiatric complications in stroke patients, affecting more than one-third of survivors of ischemic stroke (IS). Despite its high incidence, PSD is often overlooked or undertreated in clinical practice, and effective preventive measures and therapeutic interventions remain limited. Although the exact mechanisms of PSD are not fully understood, emerging evidence suggests that the gut microbiota plays a key role in regulating gut-brain communication. This has sparked great interest in the relationship between the microbiota-gut-brain axis (MGBA) and PSD, especially in the context of cerebral ischemia. In addition to the gut microbiota, another important factor is the gut barrier, which acts as a frontline sensor distinguishing between beneficial and harmful microbes, regulating inflammatory responses and immunomodulation. Based on this, this paper proposes a new approach, the microbiota-immune-barrier axis, which is not only closely related to the pathophysiology of IS but may also play a critical role in the occurrence and progression of PSD. This review aims to systematically analyze how the gut microbiota affects the integrity and function of the barrier after IS through inflammatory responses and immunomodulation, leading to the production or exacerbation of depressive symptoms in the context of cerebral ischemia. In addition, we will explore existing technologies that can assess the MGBA and potential therapeutic strategies for PSD, with the hope of providing new insights for future research and clinical interventions.